RISK MANAGEMENT IN E-BANKING SECTOR – AN ANALYTICAL STUDY - Sathyanarayana, Sathyanarayana (European Scientific Journal, ESJ, 2014)
E-banking or internet banking refers to systems that enable bank customers to access accounts and information on bank products and services through a personnel computer or other intelligent device. Information technology is the key drivers of information age. It is highly cost effective channel for delivery of banking services; it is not free from the risks. A part from cost of reduction in cost of transactions internet banking also brought about a new set of risks that too in new forms. Regulators and supervisors all over the world are aware of different types of risks in internet banking. An important and distinctive feature of internet banking is that here technology plays a significant role as a source of tool for control of risks. Because of faster and speedier information technology, there is no finality either in the type of risks or measures to control them.